Diverse Options Exist for Securing Sustainable Feedstock for Charcoal in the Global South - Mwampamba, T.H.; Njenga, M.; Doggart, N.; Meshack, C.; Dahdouh-Guebas, F.; Satyanarayana, B. (2021)
Charcoal is the primary energy used for cooking and heating in millions of homes and restaurants in the Global South. In Africa alone, which produces 65% of global production, an estimated 195million people are engaged in the production of firewood and charcoal. Despite decades of efforts to transition away from charcoal, consumption is growing and expected to increase in the foreseeable future as it continues to be the most affordable, accessible and preferred cooking fuel. Where wood supplies are diminishing, growing demand for charcoal threatens forests and forest-dependent livelihoods; it also frustrates efforts to reduce greenhouse gas emissions and curb biodiversity loss. Securing biomass that is renewable, reliable, economically viable and culturally acceptable is urgently needed in the Global South to develop sustainable charcoal sectors. In this policy brief, we present three tested approaches for producing feedstock for charcoal that can be applied to diverse contexts.